An online-enabled remote monitoring device for assessing polarization and depolarization potential behavior of cathodic protection systems in underground pipelines - Mohamad, Khairul Anuar; Haslin, Muhammad Haziq; Nordin, Mohammad Syahmi; Razali, Elfarabi; Awang Besar, Julkifli; Alias, Afishah (2024)
Metallic structures, such as pipelines and storage tanks, are among the most critical infrastructures worldwide for transporting liquids or gases. Conventional on-site inspections and monitoring methods are not effective in detecting sudden or occasional failures due to corrosion in these metallic structures. Therefore, a continuous monitoring system is necessary to provide early warnings for immediate mitigation and to monitor the cathodic protection (CP) operating conditions and its surrounding environments. A test post remote monitoring system, equipped with voltage, humidity, and battery capacity sensors is developed and integrated with an industrial internet of things (IIoT) platform. Node-RED was utilized to develop an interface for monitoring parameters collected from the system via a communication protocol. The findings indicate that the remote monitoring system can measure potential readings with a low error of within 1% comparable to a conventional multimeter. Furthermore, the system enables monitoring the polarization and depolarization potential behavior during cathodic protection operation conditions on a pipeline.